1996
DOI: 10.2166/wst.1996.0254
|View full text |Cite
|
Sign up to set email alerts
|

Hazardous waste stabilization with clean-coal technology ash residuals

Abstract: Clean coal technology by-products, collected from commercial operations under steady state conditions, are reacted at bench-scale with metal-laden hazardous wastes. Reaction conditions involve mixing calibrated weight ratios of by-product to hazardous waste with attention to minimizing added moisture. Of the 15 heavy metals monitored, lead appeared to be the element of greatest concern both from a leaching and a regulatory point of view. While leaching information is focused on lead stabilization, similar info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Several authors have shown that solidification, stabilization, and vitrification processes can be used to recycle different residues such as: radioactive residues (Garrido et al 2004); ash from incineration processes (Romero et al 1999, Kim et al 2000, Cheeseman et al 2003, galvanizing residues (Silva & Mello Castanho 2004); iron-rich resi-dues from hydrometallurgical processes, used to obtain various types of glass and ceramic glass (Pelino 2000); coal ash (Neufeld et al 1996, Cimdins et al 2000, Pereira et al 2001; fly ash (Parsa et al 1996, Barbieri et al 2000, Pisciella et al 2000, Jonker & Potgieter 2005; residues from steel-making processes, which contain Zn, Pb, Cd, Ni, and Cr, that have been mixed with clays to obtain the so-called 'ecological bricks ' (Dominguez et al 1996). Several authors have shown that solidification, stabilization, and vitrification processes can be used to recycle different residues such as: radioactive residues (Garrido et al 2004); ash from incineration processes (Romero et al 1999, Kim et al 2000, Cheeseman et al 2003, galvanizing residues (Silva & Mello Castanho 2004); iron-rich resi-dues from hydrometallurgical processes, used to obtain various types of glass and ceramic glass (Pelino 2000); coal ash (Neufeld et al 1996, Cimdins et al 2000, Pereira et al 2001; fly ash (Parsa et al 1996, Barbieri et al 2000, Pisciella et al 2000, Jonker & Potgieter 2005; residues from steel-making processes, which contain Zn, Pb, Cd, Ni, and Cr, that have been mixed with clays to obtain the so-called 'ecological bricks ' (Dominguez et al 1996).…”
Section: Waste Management and Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…Several authors have shown that solidification, stabilization, and vitrification processes can be used to recycle different residues such as: radioactive residues (Garrido et al 2004); ash from incineration processes (Romero et al 1999, Kim et al 2000, Cheeseman et al 2003, galvanizing residues (Silva & Mello Castanho 2004); iron-rich resi-dues from hydrometallurgical processes, used to obtain various types of glass and ceramic glass (Pelino 2000); coal ash (Neufeld et al 1996, Cimdins et al 2000, Pereira et al 2001; fly ash (Parsa et al 1996, Barbieri et al 2000, Pisciella et al 2000, Jonker & Potgieter 2005; residues from steel-making processes, which contain Zn, Pb, Cd, Ni, and Cr, that have been mixed with clays to obtain the so-called 'ecological bricks ' (Dominguez et al 1996). Several authors have shown that solidification, stabilization, and vitrification processes can be used to recycle different residues such as: radioactive residues (Garrido et al 2004); ash from incineration processes (Romero et al 1999, Kim et al 2000, Cheeseman et al 2003, galvanizing residues (Silva & Mello Castanho 2004); iron-rich resi-dues from hydrometallurgical processes, used to obtain various types of glass and ceramic glass (Pelino 2000); coal ash (Neufeld et al 1996, Cimdins et al 2000, Pereira et al 2001; fly ash (Parsa et al 1996, Barbieri et al 2000, Pisciella et al 2000, Jonker & Potgieter 2005; residues from steel-making processes, which contain Zn, Pb, Cd, Ni, and Cr, that have been mixed with clays to obtain the so-called 'ecological bricks ' (Dominguez et al 1996).…”
Section: Waste Management and Researchmentioning
confidence: 99%
“…The aim of this process is to immobilize hazardous substances that are present in residues (Neufeld et al 1996). The aim of this process is to immobilize hazardous substances that are present in residues (Neufeld et al 1996).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations